Organizational culture as one of the main factors for the successful management of protection - Živković, Snežana B; Ivanova, Tatjana (Serbian Journal of Management, 2016)
The goal of this research is to establish the influence of organizational culture on the system of safety and health at work. The research sample included 556 respondents of various activities in Russia.Based on the results, it can be concluded that there is a statistically significant connection of the Attitude towards occupational safety with 5 out of 7 aspects of organizational culture, as well as with the general factor of Usefulness of the manner of management. In addition, there is a statistically significant connection to age, total years of service and qualifications. Through a comparative analysis of results acquired in the Republic of Serbia and Russia, differences in attitudes towards safety and health activities at work were acquired i.e. there is a difference between the average answers of respondents from Serbia and Russia in the Attitude towards occupational safety which is on average slightly more prominent in respondents from Serbia. In relation to organizational culture aspects, there are differences in Vision, Credibility, Feedback and recognition as well as Responsibility. Respondents from Serbia have higher average values on all these measures, but all the differences are small (all effect sizes are below 0.2).
Keywords: Safety Management; Serbia; safety and health; organizational culture